Sustainability-driven entrepreneurship: Principles of organization design - Parrish, Bradley D. (Journal of business venturing, 2010)
Concern about whether the social–ecological processes that provide for human wellbeing can be sustained has given rise to sustainable development as a broad social goal. As a dynamic force for change, entrepreneurship is increasingly expected to contribute to this goal. This article reports on the results of an intensive empirical study investigating the organization design expertise necessary for sustainability-driven entrepreneurs to succeed in a competitive market context. Results reveal five principles of organization design that diverge in important ways from the conventional principles of entrepreneurship, suggesting the expertise required for venture success differs depending on entrepreneurial values and motives.